Tectonic Stress as the Driving Mechanism for Dike Opening in an Oblique Rift Setting: A Deformation Model of the 2021 Fagradalsfjall Dike, Iceland - Sonja H. M. Greiner; Freysteinn Sigmundsson; Halldór Geirsson; Steffi Burchardt; Olivier Galland (Geophysical Research Letters)
Abstract Repeated dike‐intrusions often occur in zones where extensional stress has accumulated. Still, geodetic modeling of observed dike‐induced ground deformation often ignores the contribution of tectonic stress. On the obliquely spreading Reykjanes Peninsula, Iceland, tectonic strain build‐up had been geodetically documented for three decades when a magmatic dike formed at Fagradalsfjall in 2021. We explore the contribution of tectonic stress on dike emplacement in a viscoelastic three‐dimensional Finite‐Element deformation model. Tectonic stress accumulation is initially simulated through plate motion, and later partially released by opening of a segmented rectangular dike. We find that surface deformation can be largely reproduced by releasing ∼60% of the accumulated tectonic stress. Partial stress release and low magma overpressure are consistent with successive dike intrusions and low‐intensity eruptions in the area. Our model provides an approach to consistently model stress‐release constrained by surface deformation.